The impact of narrow personality traits on entrepreneurial intention in developing countries: A comparison of Turkish and Iranian undergraduate students using ordered discrete choice models - Ali Kemal Çelik; Tayfun Yıldız; Zafer Aykanat; Siamak Kazemzadeh (European Research on Management and Business Economics (ERMBE), 2021)
This study aimed to examine the potential determinants of the entrepreneurial intention (EI) levels ofTurkish and Iranian undergraduate students with an emphasis on the narrow personality traits thatcould predict such students' EI levels. For this purpose, a well-established written questionnaire wasadministered to a total of 875 undergraduate students from both countries. Due to the ordered natureof the dependent variable, the data were analyzed using the ordered logit, generalized ordered logit,and partial proportional odds models. The results of the study showed significant differences betweenthe Turkish and Iranian undergraduate students' EI levels. That is, the presence of an entrepreneur inthe family increased the Turkish undergraduate students' EI levels whereas the Turkish undergraduatestudents whose household heads were government officials or retirees had lower EI levels than thosewhose parents were self-employed. The Turkish undergraduate students who saw themselves as havingmuch enthusiasm and having the tendency to become tense and to do things efficiently had a higherintention to found a business venture in the near future compared to those who did not have such traits.In contrast, the Turkish students who saw themselves as having the tendency to persevere until theirtask is finished, to be moody, and to make plans and implement them had lower EI levels than thosewho did not have these traits. Openness (with significant narrow personality traits such as having thetendency to be original, to come up with new ideas, and to have an active imagination) was found to bethe Big Five personality trait with the greatest positive impact on the Iranian undergraduate students'EI levels whereas the Iranian undergraduate students who saw themselves as ingenious, deep thinkers,and worriers had lower EI levels. It was also shown in this study that the Iranian undergraduate studentswith a monthly income from a job in addition to their stipend from their family were more likely to havehigher EI levels than those whose monthly funds came only from their parents. In addition, the maleIranian students were found to have lower EI levels than their female counterparts. This study contributedto the existing literature by conducting a cross-cultural comparison of two developing countries usingthe ordered discrete choice modeling approaches, and its empirical findings may assist policymakers incoming up with effective policies for promoting entrepreneurship.
Keywords: L26; C25; 650; Entrepreneurial intention; Discrete choice modeling; Narrow personality traits; tDeveloping country